1966
DOI: 10.1007/bf01250153
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of the cytopathic changes produced in human amnion cell cultures by the molluscum contagiosum virus

Abstract: ~: Molluscum contagiosum is an infectious disease of the human skin and is characterized by a localized proliferation of the epidermis forming a lobu]ated and umbilicated papule, which presents certain similarities to a localized neoplasm.The disease is caused by a virus (1, 2) which, studied by electron microscopic and histochemical procedures (3--10), has been shown to possess the basic characters of the pox-virus group.So far, all attempts to propagate the molluscum contagiosum virus in tissue cultures or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1967
1967
1997
1997

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…However, the results of serological studies (3, 19) have indicated the absence of an antigenic relationship with vaccinia, cowpox, or fowlpox viruses, and virus extracted from dermal lesions has been found incapable of "reactivation" of heat-inactivated vaccinia virus in primary amnion cells (15). There are several reports of attempts to isolate and propagate MCV in cell culture (4,5,13,20,24,28). Such studies have shown that the virus induces nontransmissible cytopathic changes in cells of different species without the production of infectious progeny virus.…”
mentioning
confidence: 99%
“…However, the results of serological studies (3, 19) have indicated the absence of an antigenic relationship with vaccinia, cowpox, or fowlpox viruses, and virus extracted from dermal lesions has been found incapable of "reactivation" of heat-inactivated vaccinia virus in primary amnion cells (15). There are several reports of attempts to isolate and propagate MCV in cell culture (4,5,13,20,24,28). Such studies have shown that the virus induces nontransmissible cytopathic changes in cells of different species without the production of infectious progeny virus.…”
mentioning
confidence: 99%